THE ROLE OF FAMILY AND SCHOOL IN ENGLISH LANGUAGE LEARNER IDENTITY CONSTRUCTION: AN INDONESIAN CASE - Al Mubarokah, Laelah; Prasetya, Willy (PEOPLE: International Journal of Social Sciences, 2020)
In the process of learning English, a learner constantly reshapes his/her identity as he/she goes through different learning experiences. A particular experience may be added as a new part to a learner’s perceived identity or replace another part of it. The present study examined how an Indonesian reconstructed her identity as an English language learner (ELL) as she went through various learning experiences since childhood to university level in two different countries. In-depth interview was conducted to collect the participant’s account on her experiences, followed by several online correspondences within two months after the interview was conducted. The results of this study indicated that parental support and school policy and environment played an important role in reshaping the participant’s identity. Her identity construction was then explained using Gee’s (2000) four perspectives of identity. This study extends the research on learner identity particularly in Indonesian context or any other contexts with nearly similar characteristics.